Teacher-Rated Executive Functions, Gender and Relative Age: Independent and Interactive Effects on Observed Fundamental Motor Skills in Kindergarteners - Escolano-Pérez, Elena; Sánchez-López, Carmen R.; Herrero-Nivela, Maria Luisa (Frontiers in Psychology, 2022)
Fundamental motor skills (FMS) of children can be affected by different variables, such as executive functions, gender and relative age. However, the effects of these variables on FMS have been scarce studied, especially in early childhood, and show inconsistent results. To clarify these relationships, this study was carried out. Its aim was to analyze whether executive functions, gender and relative age influenced FMS in 43 Spanish kindergarteners. A multimethod and mixed methods approach was used. Kindergarteners' teachers completed the Childhood Executive Functioning Inventory to know the children level of executive functions (working memory and inhibition control). Kindergarteners' parents complimented ad hoc questionnaire reporting the children gender and birth data (to know their relative age). A Nomothetic/Punctual/Multidimensional observational design was used to observe children FMS in their habitual motor sessions at school. Two-way ANOVAs were performed to know the independent and interactive effects of working memory level (lower/higher), inhibition control level (lower/higher), gender (boys/girls) and relative age (according to the birth semester in the year) on FMS. Results showed these variables have independent and interactive effects on some FMS, but not on others. FMS influenced by these variables vary depending what independent variable(s) is/are considered. Therefore, it can be concluded that the influences of teacher-rated executive functions, gender and relative age on observed FMS in kindergarteners are complex and specific. Results obtained must be taken into to design and implement instructional and intervention strategies, as well as educational and sport policy changes, especially in early childhood, when FMS are more malleable.